Filón de Biblos y la imaginación literaria: la naturaleza retórica de la "Historia fenicia" - Rodríguez Horrillo, Miguel Ángel (Eirene: studia graeca et latina, 2012)
The fragments of Philo’s 'Phoenician History' have a content that the research on Eastern mythologies seems to confirm. However, the way in which Philo affirmed he found such information, as well as the euhemerist perspective the fragments present, have led no little suspicion about its authenticity. In order to clarify this paradox, we explore the literary nature of these fragments, trying to link these fabulous features to the literary essence of historiography in this period, in which accurate information could be presented as invented. The examination of the style led us to conclude that it imitates the features of the archaic Greek literature, in order to recreate the great literature of other times creating something new. Also, the fabulous circumstances of the discovery of the lost work of Sanchuniathon acquire their significance as a literary prologue that facilitates the reader’s understanding of the two-level lectures that presents the 'Phoenician History'. So, Philo creates a literary work that imitates the stylistic characteristics of the ancient Greek mythical genealogies, also presenting genuine contents of the Eastern mythology.